An Embroidered Cartography: Using Phenomenologically Art-Led Methods to Explore the Futures Sense of Memory for Tertiary Career Education - Westacott, Marguerite (Art/Research International)

(untitled) (University of Alberta, 2026)
Drawing from the fields of career education, futures studies, and visual art, this article is an interdisciplinary pilgrimage through scholarly and creative qualitative methods of research. It conveys the intersections of heuristic inquiry (as landmarks), autoethnography (the personal as universal) and phenomenologically art-led process (as interlocutor with subconscious and embodied knowing). The article shares the author’s exploration of the conceptual notion of the futures sense of memory—one of five cultural senses that underpin an innate anticipatory relationship with the future. Emergent data from art-led process is discussed with relevance to implications on practice in career education in tertiary pedagogy and curriculum.